Influence of array interspacing on the force required for successful microneedle skin penetration: Theoretical and practical approaches. Issue 4 (28th January 2013) - Olatunji, Ololade; Das, Diganta B.; Garland, Martin J.; Belaid, Luc; Donnelly, Ryan F.
Abstract Insertion behaviour of microneedle (MN) arrays depends upon the mechanical properties of the skin and, MN geometry and distribution in an array. In addressing this issue, this paper studies MN array insertion mechanism into skin and provides a simple quantitative basis to relate the insertion force with distance between two MNs. The presented framework is based on drawing an analogy between a beam on an elastic foundation and mechanism of needle insertion, where insertion force is separated into different components. A theoretical analysis indicates that insertion force decreases as interspacing increases. For a specified skin type, insertion force decreased from 0.029 to 0.028 N/MN when interspacing at MN tip was increased from 50 μm (350 μm at MN base) to 150 μm (450 μm at MN base). However, dependence of insertion force seems to decrease as the interspacing is increased beyond 150 μm. To assess the validity of the proposed model, a series of experiments was carried out to determine the force required for skin insertion of MN. Experiments performed at insertion speed of 0.5 and 1.0 mm/s yielded insertion force values of 0.030 and 0.0216 N, respectively, for 30 μm interspacing at MN base (330 μm interspacing at tip) and 0.028 and 0.0214 N, respectively, for 600 μm interspacing at MN base (900 μm interspacing at tip). Results from theoretical analysis and finite element modelling agree well with experimental results, which show MN interspacing only begins to affect insertion force at low interspacing (<150 μm interspacing at MN base). This model provides a framework for optimising MN devices, and should aid development of suitable application method and determination of force for reliable insertion into skin. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:1209–1221, 2013